Sanctions Against the Board of Directors who do not Implement the Decisions of the General Meeting of Shareholders (GMS) - Ariwibowo, Muhammad Rizaldhi; Malikhatun, Siti (Budapest International Research and Critics University, 2021)
The General Meeting of Shareholders that held by PT. Cengkeh Zanzibar concerning limited liability companies is not appropriately implemented by the parties concerned. In this matter, the Directors do not implement the GMS decision, which resulted in losses to the company. This study is written to discover the responsibility of the Directors from some losses to the company. The methodology of this study is normative juridical, which also with some interviews. This study concludes that the Main Director is willing to resign and looking for the new one.